Group counseling intervention module cognitive behavioral therapy effectiveness in addressing the problems of body dissatisfaction, anxiety and self-esteem in higher education institution teenagers - Terence, Nordiana; Ayub, Norzihan; Kimong, Patricia (Universitas Majalengka, 2024)
This pilot study examines body image dissatisfaction, anxiety, and self-esteem, particularly among university and college students, which can significantly impact their mental well-being. Obsession with weight satisfaction and physical attractiveness can lead to depression, eating disorders, and social disorders. Twenty Psychology and Education students participated in this study, using tools such as the multidimensional body self-relations questionnaire-appearance scale, the physical appearance state and trait anxiety scale, and the body esteem scale for adolescents and adults. Additionally, a Cognitive Behavioral Group Counseling Intervention Module was utilized to restructure thinking and modify behavior. The module results of 0.897 suggested that this intervention can help individuals change their assumptions and beliefs regarding self-image dissatisfaction, particularly on physical appearance.